Radiofrequency ablation as a minimally invasive procedure in the treatment of twin reversed arterial perfusion sequence in twin pregnancy. Issue 4 (10th May 2012) - Weichert, Alexander; Kalache, Karim; Hein, Patrick; Brauer, Martin; Hinkson, Larry; Henrich, Wolfgang
Abstract Twin reversed arterial perfusion sequence is a rare anomaly of monochorionic multiple pregnancies affecting 1 of 35, 000 pregnancies and 1% of monochorionic twin pregnancies. In this condition the affected twin has lethal malformations including poor or absent heart development and is reversely perfused by a structurally normal co‐twin. We report a case of a 21‐year‐old woman with a monochorionic twin pregnancy affected by twin reversed arterial perfusion sequence. This case highlights the therapeutic options and the management by radiofrequency ablation, which has been shown to be an easy and reliable technique with a high success rate compared with technically demanding fetoscopic procedures. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound, 2013